2022
DOI: 10.3390/ijms23074042
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Genetic Biomarkers Predicting Response to Anti-Vascular Endothelial Growth Factor Injections in Diabetic Macular Edema

Abstract: Intraocular anti-vascular endothelial growth factor (VEGF) therapies are the front-line treatment for diabetic macular edema (DME); however, treatment response varies widely. This study aimed to identify genetic determinants associated with anti-VEGF treatment response in DME. We performed a genome-wide association study on 220 Australian patients with DME treated with anti-VEGF therapy, genotyped on the Illumina Global Screening Array, and imputed to the Haplotype Reference Consortium panel. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Previous epidemiological studies established that the prevalence of DME increases along with the duration of diabetes [13,23]. Similar to our study results, DM duration has been reported as a negative predictor of anti-VEGF treatment response in DME [18,36]. Eyes with a longer duration of DM are more likely to be chronically exposed to a DME- [37] and a transition from an acute inflammatory phase to a more treatment-resistant chronic inflammatory phase [38,39].…”
supporting
confidence: 89%
“…Previous epidemiological studies established that the prevalence of DME increases along with the duration of diabetes [13,23]. Similar to our study results, DM duration has been reported as a negative predictor of anti-VEGF treatment response in DME [18,36]. Eyes with a longer duration of DM are more likely to be chronically exposed to a DME- [37] and a transition from an acute inflammatory phase to a more treatment-resistant chronic inflammatory phase [38,39].…”
supporting
confidence: 89%
“…It is therefore clear that other clinical, demographic, genetic and/or epigenetic factors are involved. Studies exploring such potential risk factors are required and are beginning to emerge [ 78 , 79 ]. Further, less than a third of DME patients (31.85%) showed combined response (functional and anatomical) with a weak negative correlation (Correlation coefficient =-0.30) observed between the two outcome categories.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that there have been exciting developments in the field of DR genetics in recent years. These advancements include exome sequencing for rare and functional variants [ 15 ], and a more in-depth analysis of DR GWAS datasets has provided further understanding of the underlying pathological pathways [ 52 ], causal factors for DR [ 53 , 54 , 55 ], ability to predict DR using polygenic risk scores [ 56 ], and pharmacogenetic responses to treatment [ 57 ].…”
Section: Resultsmentioning
confidence: 99%